(untitled) (Context: Journal of Interdisciplinary Studies, 2024)
Despite the achievements of Western civilisation and regulations requiring gender and religious equality, Europe still exhibits a low tolerance for Muslim dress practices. France may be considered a leader in this, as, after banning the hijab in institutions, it has also prohibited face coverings in public. The United Kingdom (UK) stands as a traditional European opponent to the French model of laicism. In the UK, wearing the hijab is allowed in public schools and at the workplace. Meanwhile, authoritarian states in the Muslim world impose conservative dress codes on women, the most radical of which have been enacted by the Kingdom of Saudi Arabia and the Islamic Republic of Iran. Bosnia and Herzegovina, a country with an indigenous Muslim population, is trying to find its own path. Between secularism and religiosity, certain legislative solutions in Bosnia and Herzegovina lean toward a form of secularism.